The Difficult Application of Modern Education Technology from the Point View of the Members of a Teaching Staff (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The current research aims to identify the difficulties of using a sample of faculty members in the Faculty of Basic Education / Mustansiriya University for modern education technology in their teaching, and the extent of their actual use of the variables (academic qualification, academic qualification, specialization and years of experience). The researchers designed a research tool to identify the views of the members of the teaching staff at the Faculty of Basic Education after their distribution and to verify the validity and truthfulness of the questionnaire by presenting them to a group of arbitrators, professors of education, professors of psychology, measurement and evaluation, And a group of faculty members included in the sample of the study. The questionnaire contains the difficulties that prevent the effective use of technology from the point of view of faculty members and whether there is a relationship between variables (scientific title, specialization, academic qualification, and years of experience in university education(.The percentages, frequencies and weighted mean were used to analyze the data. The researchers also used the Wilcoxon test to identify the mean differences between the study groups using the spss program.The results of the research revealed the existence of some obstacles that hinder the use of teaching technology by teaching staff members. The most important of these are the lack of necessary equipment and infrastructure, some of which are related to the weakness of training courses in the use of modern teaching technology in teaching. The research presented a number of recommendations and suggestions.